Characteristics of cathodic polarization at Pt/YSZ interface without the effect of electrode microstructure - Yoon, SP; Nam, SW; Kim, SG; Hong, SA; Hyun, SH (ELSEVIER, 2003)
The characteristics of cathodic polarization at the Pt/yttria stabilized zirconia (YSZ) interface have been evaluated with different electrode microstructures by ac impedance analysis. The measurements were carried out at the temperatures of 873-1273 K and oxygen partial pressure (P-O2) in the range of 0.01-1 atm. From the results of impedance analysis, it was found that gas phase diffusion can be involved in two different ways, such as boundary-layer diffusion and pore diffusion. When the gas phase diffusion was effectively eliminated from the total electrode resistance (R-e1), we observed the same dependences of temperature and oxygen partial pressure regardless of their different electrode microstructures. In the high temperature (1073-1273 K) and low oxygen partial pressure regions (<0.01 atm P-O2), the cathode reactions included two major reactions: gas phase diffusion and direct adsorption reaction. In direct adsorption reaction oxygen molecules are directly adsorbed from the gas phase and dissociate on oxygen vacancies, which are located at the triple phase boundaries (TPB). In the low temperature (<973 K) and high oxygen partial pressure region (similar to1 atm P-O2), the cathode reaction is dominated by the dissociation of oxygen molecules at the Pt/YSZ interface. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: PT,O-2(G)/STABILIZED ZIRCONIA INTERFACES; CALCIA-STABILIZED ZIRCONIA; DIOXIDE-OXYGEN REACTIONS; PLATINUM-ELECTRODES; ELECTROCHEMICAL MEASUREMENTS; ADSORPTION; DIFFUSION; KINETICS; SYSTEM; SOLUBILITY